Nonketotic hyperglycinemia: a report of three cases - Coşkun, Turgay; Özalp, İmran; Mönch, Eberhard; Yalaz, Kalbiye (The Turkish Journal of Pediatrics, 1988)
Nonketotic hyperglycinemia (NKH) is an inherited disorder of glycine metabolism. It usually presents with hypotonia, generalized myoclonic seizures, respiratory distress and hiccup in the neonatal period, and is characterized clinically by elevated concentrations of glycine in plasma, spinal fluid and urine. The elevation of CSF glycine and the absence of ketoacidosis are the useful tools in distinguishing NKH from other hyperglycinemic states. In this report, the clinical and laboratory findings of three cases with NKH are presented. According to the data obtained from these cases and from the literature, it is obvious that our current state of knowledge of this disorder is incomplete. Therefore, a sustained and effective therapy awaits further research on the etiology of NKH and the use of new pharmacologic agents.
Keywords: nonketotic hyperglycinemia; metabolic disease